E-LKPD: PENGEMBANGANNYA PADA TEMA 2 UDARA BERSIH BAGI PERNAPASAN KELAS V SD/MI (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
E-LKPD: Development on Theme 2 Clean Air for Breathing Class V SD/MI Abstract This study uses development research using the Borg and Gall model. The tools used are questionnaires and documentation. The questionnaire consisted of media experts, material experts and educator responses. The data analysis technique used descriptive quantitative. The results showed that the development of E-LKPD on the theme of 2 clean air for breathing with the assessment of media experts was 82.5% in the very appropriate category and material experts 81.75% very well. In addition, the response of educators is 84.89% with a very decent category, field trials of 81.17% with very interesting interpretation criteria. So that the E-LKPD on theme 2 clean air for breathing that has been developed is very feasible and very interesting as learning material during the learning process. Keywords: E-LKPD, theme tow